Tokirikuoto (Dang-Gui-Liu-Huang-Tang) :How it was formulated and its clinical indications seen in Chinese medical classics - KOSUGE, Takaaki; YOSHIDA, Kazuhisa; UEMATSU, Mikum; TSUKADA, Sinpei; TSUCHIYA, Takashi; HASHIGUCHI, Makoto; KUWANA, Kazuyoshi; ITAKURA, Hidetoshi; NARA, Kazuhiko; SAITO, Teruo; FUKUSHIMA, Atushi; MIURA, Oto; et al. (Kampo Medicine, 2010)
Dang Gui Liu Huang Tang (in the Lan Shi Mi Cang written by Li Dong-yuan) is a common medicine for treating night sweats. We describe its historical development and therapeutic uses. The use of Huan qi (Radix Astragali sen Hedysari) is based on the Han-Sui dynasty medical principle that night sweats are mainly caused by Deficiency of Yang. Herbs to enrich the lood and Yin, Dang gui (Radix Angelicae Sinesis), Seng di huang (Radix Remannia), Shu di huang Radix Rehmannia preparata) were later added because Son dynasty physicians mentioned that Yin deficiency caused night sweats. The addition of heat-reducing herbs, such as Huang lian (Rhizoma Coptidis), was based on the Song dynasty theory that night sweats are caused by pathologic heat in the body, which forces body fluid out of the skin. In the same period, the herbal medicine called Da Jin Hua Wan created by Liu Wansu, and this greatly influenced the principles for treating night sweats. The clearest explanation can be found in the medical treaties Huang Di Nei Jing Su Wen, and Xuan Ming Lun. This medical combination was based on medical theories from a number of historical periods, which may explain its effectiveness. Dang Gui Liu Huang Tang is not effective against types of weak heat (Dan xin xin fa), severe vital Qi Deficiency (Zhang shi yang), or serious deficiency of Yin (Yi xue xin wu). It sometimes hurts Pi and Wei (digestive system). It is useful in the treatment of spontaneous perspiration (Yi xue zheng zhuang, Jin xue quan shu). In summary, this medicine is most effective when the seriousness of heat and Yin deficiency are almost equal and a slight Qi Deficiency exists, or in cases of spontaneous perspiration.